2018
DOI: 10.1186/s13034-018-0254-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of electroconvulsive therapy in adolescents with schizophrenia in China

Abstract: BackgroundElectroconvulsive therapy (ECT) is an effective treatment for psychiatric disorders such as schizophrenia, major depression and bipolar disorder. However, few studies have addressed the use of ECT in adolescents with schizophrenia. The aims of our study were to investigate the frequency of ECT, and its relationship with clinical and demographic correlates among adolescents with schizophrenia in China.MethodsThe study was a retrospective study and conducted in the Child and Adolescent Psychiatry Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
2
13
1
Order By: Relevance
“…In our study, although the efficacy of ECT in the treatment of SCZ was lower than affective disorders, the results showed that the majority of adolescents with SCZ had experienced clinically significant improvement. Wang et al reviewed adolescents with SCZ treated by ECT in China (326 samples), and their results suggested that the response rate was 65%, which was very close to our results (24). A retrospective chart review evaluated the clinical profile of adolescents who had received ECT, the results showed that the rate of remission for SCZ was lower than MDD and mania, which was similar to our results (29).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, although the efficacy of ECT in the treatment of SCZ was lower than affective disorders, the results showed that the majority of adolescents with SCZ had experienced clinically significant improvement. Wang et al reviewed adolescents with SCZ treated by ECT in China (326 samples), and their results suggested that the response rate was 65%, which was very close to our results (24). A retrospective chart review evaluated the clinical profile of adolescents who had received ECT, the results showed that the rate of remission for SCZ was lower than MDD and mania, which was similar to our results (29).…”
Section: Discussionsupporting
confidence: 89%
“…A recent study (835 samples) reviewed adolescents with schizophrenia from 2007 to 2016 in a single Chinese academic medical center. This study found that the frequency of ECT use was 49.2% and ECT use was independently and positively associated with gender, and high risk for suicide (24). A retrospective study examined the association between baseline futures and clinical outcomes, the results suggested that ECT is safe and efficacy, but the clinical response was not predicted by demographic data (23).…”
Section: Introductionmentioning
confidence: 99%
“…The practice parameter of the American Association of Child and Adolescent Psychiatry recommends electroconvulsive therapy (ECT) for adolescents in resistant cases of major depression [8]. However, ECT is less frequently used [4,9] due to cognitive side effects, prolonged seizure, and anesthetic complications [4,10]. As a result, there is an increasing interest in novel treatment approaches for major depression.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of sessions and the duration of treatment depend on the pathology and the patient's response rate, and the placement of the electrodes can be unilateral or bilateral, with bilateral placement appearing to be more effective at lower doses in reducing depressive symptoms, however, can lead to a transient impairment of anterograde memory, reduced with unilateral positioning 1 . The decision for therapy is influenced by side effects, costs and hospital guidelines; the grading of risk depends on the occurrence of comorbidities and the patient's need, and the effectiveness of treatment, after remission of symptoms with ECT, can be maintained with the use of antidepressants or lithium 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite being relatively safe and with little long-term negative neuropsychological influence, ECT is considered an invasive treatment and may have cognitive impairment as side effects, mainly transient anterograde memory impairment; delirium; pain and/or musculoskeletal injury, prolonged seizures and complications associated with anesthesia, so the patient must be constantly supervised by the team, with the anesthesiologist, during the procedure 3,4 .…”
Section: Introductionmentioning
confidence: 99%